SANKSI HUKUM TERHADAP PELAKU KEJAHATAN KEMANUSIAAN DI INDONESIA (Faculty of Law, University of Palembang, 2023)
A crime against humanity according to Article 9 of Law Number 26 of 2000 concerning the Human Rights Court is an act committed as part of a widespread or systematic attack in which it is known that the attack was directed directly against the civilian population. The problem in this paper is about legal sanctions against perpetrators of crimes against humanity in Indonesia based on Law Number 26 of 2000 concerning the Human Rights Court?. The legal sanctions are contained in Law No. 26 of 2000 that the punishment that can be imposed is regulated in Chapter VII concerning Criminal Provisions which includes Articles 36 to 42. Criminal threats are regulated in Articles 36 to 40 of Law No. 26 of 2000 about the Human Rights Court.